In Situ Monitoring of the Antibacterial Activity of a Copper–Silver Alloy Using Confocal Laser Scanning Microscopy and pH Microsensors - Nicole Ciacotich; Kasper Nørskov Kragh; Mads Lichtenberg; Jens Edward Tesdorpf; Thomas Bjarnsholt; Lone Gram (Global Challenges, 2019)
Abstract The antibacterial efficacy of a copper–silver alloy coating under conditions resembling build up of dry surface bacterial biofilms is successfully demonstrated according to US EPA test methods with a ≥99.9% reduction of test organisms over a 24 h period. A tailor‐made confocal imaging protocol is designed to visualize in situ the killing of bacterial biofilms at the copper–silver alloy surface and monitor the kinetics for 100 min. The copper–silver alloy coating eradicates a biofilm of Gram‐positive bacteria within 5 min while a biofilm of Gram‐negative bacteria are killed more slowly. In situ pH monitoring indicates a 2‐log units increase at the interface between the metallic surface and bacterial biofilm; however, the viability of the bacteria is not directly affected by this raise (pH 8.0–9.5) when tested in buffer. The OH− production, as a result of the interaction between the electrochemically active surface and the bacterial biofilm under environmental conditions, is thus one aspect of the contact‐mediated killing of the copper–silver alloy coating and not the direct cause of the observed antibacterial efficacy. The combination of oxidation of bacterial cells, release of copper ions, and local pH raise characterizes the antibacterial activity of the copper–silver alloy‐coated dry surface.